„Takie jak w rzeczywistości”. Obraz fotograficzny - obiektywne odwzorowanie czy subiektywna kreacja? Fotografia w badaniach archeologicznych - Markiewicz, Małgorzata (Folia Praehistorica Posnaniensia, 2023)
The article reviews the current state of knowledge on photography and the use of photographs in archaeological research. The discovery of photography was a breakthrough in the history of archaeology. The mechanical method of image registration, considered to be devoid of subjective human intervention, was supposed to guarantee the neutrality and objectivity of the visual representation. Belief in realism of photography has led to it becoming the primary form of documentation in archaeology, for both the research process and the relics themselves. This article will attempt to answer the question of whether we can trust the reality captured by the photographer? The reading of a photograph is done through culturally shaped codes. The ability to decipher those codes depends on the knowledge and experience of the recipient. The photographic image relies on the photographer’s subjective view of the subject, as well as the medium used, which influences the nature of the representation.